2013
DOI: 10.1093/infdis/jis927
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Update on Hepatitis C Infection in Persons Living With or at Risk of HIV Infection

Abstract: Due to shared routes of transmission, coinfection with both human immunodeficiency virus type 1 (HIV-1) and hepatitis C virus (HCV) is relatively common and results in accelerated liver disease, driving morbidity and mortality. Deaths related to HCV now exceed deaths related to HIV in the United States, and co-infected patients bear a significant proportion of that mortality. This burden may be addressed by novel antiviral therapies that promise increased rates of cure or by enhanced access to liver transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 19 publications
(20 reference statements)
1
82
0
2
Order By: Relevance
“…The percentage of all HIV infected people who also have HCV ranges from 15% to 30%, and one study reported that 37% of people with HIV were co-infected with HCV. 1,2 Unrecognized HIV/HCV co-infection has serious implications on liver health, as it may accelerate the progression of HCV liver disease. 1,2 Early detection of people co-infected with HIV and HCV is essential in managing treatment of these infections.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of all HIV infected people who also have HCV ranges from 15% to 30%, and one study reported that 37% of people with HIV were co-infected with HCV. 1,2 Unrecognized HIV/HCV co-infection has serious implications on liver health, as it may accelerate the progression of HCV liver disease. 1,2 Early detection of people co-infected with HIV and HCV is essential in managing treatment of these infections.…”
mentioning
confidence: 99%
“…1,2 Unrecognized HIV/HCV co-infection has serious implications on liver health, as it may accelerate the progression of HCV liver disease. 1,2 Early detection of people co-infected with HIV and HCV is essential in managing treatment of these infections. Thus in 2009, the European Aids Clinical Society (EACS) guidelines 3 introduced the notion of systematic annual HCV screening among HIV-infected patients.…”
mentioning
confidence: 99%
“…The interplay between both the viruses is complex and usually leads to accelerated forms of HIV-1 disease as well as HCV disease [21]. In fact, some recent reports have suggested that HCV-related deaths are greater than HIV-1-related deaths in the United States, and that the HIV-1/HCV co-infected individuals are the ones bearing a significant portion of the mortality [40]. Accelerated liver disease, higher viral loads, and differential therapeutic regimens are some of the specific challenges encountered during HIV-1/HCV coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…In Deutschland sind ca. 10 000 (15 % aller HIV-Patienten), in den USA 240 000 (30 % aller HIV-Infizierten) mit HCV koinfiziert [73]. Die wenigsten dieser Patienten sind adäquat therapiert und es wird angenommen, dass eine HCV-Koinfektion mit einem beschleunigten Verlauf der HIV-Infektion bei unbehandelten Patienten assoziiert sein könnte [74].…”
Section: Bedeutung Von Komorbiditätenunclassified